Surgical Approach to Primary Tumors of the Chest Wall in Children and Adolescents: 30 Years of Mono-Institutional Experience. Issue 1 (January 2016) - Girelli, Lara; Luksch, Roberto; Podda, Marta G.; Meazza, Cristina; Puma, Nadia; Scanagatta, Paolo; Pecori, Emilia; Diletto, Barbara; Galeone, Carlotta; Massimino, Maura; Pastorino, Ugo
Aims and background: Chest wall reconstruction after surgical resection for malignancies in children is a challenge for surgeons because of growth-related complications. The aim of this study is to analyze the surgical treatment and outcomes of 30 pediatric and adolescent patients treated at Fondazione IRCCS Istituto Nazionale dei Tumori, Milan, Italy, over a 30-year period. Methods: Pediatric patients undergoing chest wall resection were retrospectively reviewed and selected for malignant primary tumor. Endpoints were survival, recurrences, and long-term results. We also reported the use of the innovative rib-like technique in 2 young patients. Results: Twenty-one patients were male. Median age was 13.7 years. Eleven patients (37%) presented with a chest wall mass. Twenty-six (87%) had Ewing sarcoma family tumors. Twenty-eight (94%) received neoadjuvant chemotherapy after histologic diagnosis. One rib was resected in 13 cases; 2 or 3 contiguous ribs in 8 cases. No postoperative mortality was observed and the complication rate was 40%. Overall survival was 85.2% (95% confidence interval [CI] 65.2%-94.2%) at 5 and 10 years. Relapse occurred in 7 patients. The 5-year disease-free survival rate was 82% (95% CI 62%-92%). Conclusions: Long-term survival is achievable for chest wall tumors in a high-volume referral center where a multimodal treatment should be set to reach the best result. As advances in medical treatment have increased survival, surgical techniques must ensure a lasting functional result. When refining the reconstruction techniques, such as the rib-like approach, it is necessary to expand the options of curative surgery for young patients.